2011
DOI: 10.1111/j.1582-4934.2010.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet‐induced liver steatosis promotes an increase in liver mitochondrial biogenesis in response to hypoxia

Abstract: Mitochondrial DNA (mtDNA) copy number plays a key role in the pathophysiology of metabolic syndrome-related phenotypes, but its role in non-alcoholic fatty liver disease (NAFLD) is not well understood. We evaluated the molecular mechanisms that may be involved in the regulation of liver mtDNA content in a high-fat-induced rat model of NAFLD. In particular, we tested the hypothesis that liver mtDNA copy number is associated with liver expression of HIF-1α. Rats were given either standard chow diet (SCD, n= 10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 41 publications
8
77
0
1
Order By: Relevance
“…This observation is in line with our previous report in an animal model of diet-induced fatty liver about a compensatory increase in the liver mtDNA content in the absence of IR to accommodate the metabolic load. 28 Similar results have been shown to occur in skeletal muscle until the development of IR. 29 However, when IR is established, the decrease in mtDNA content is a common finding, even in leukocytes.…”
Section: Discussionsupporting
confidence: 69%
“…This observation is in line with our previous report in an animal model of diet-induced fatty liver about a compensatory increase in the liver mtDNA content in the absence of IR to accommodate the metabolic load. 28 Similar results have been shown to occur in skeletal muscle until the development of IR. 29 However, when IR is established, the decrease in mtDNA content is a common finding, even in leukocytes.…”
Section: Discussionsupporting
confidence: 69%
“…In agreement with these observations, Han et al reported that liver mitochondria undergo dynamic alterations following chronic alcohol feeding in mice that include increased mitochondrial NAD + and NADH levels with enhanced mitochondrial biogenesis in the liver to adapt to metabolic stress [ 74 ]. Our group observed a similar fi nding in rats, demonstrating that in rodents, metabolic insults, like high-fat diet, promote an increase in liver mitochondrial biogenesis in response to hypoxia via HIF-1alpha, probably to enhance the mitochondrial function and to accommodate the metabolic stress [ 75 ]. Nevertheless, once the NAFLD is established in humans and the disease progresses to NASH, mitochondrial DNA content is signifi cantly reduced in the liver, suggesting that the advanced disease is associated with a loss of the adaptive mechanism for the metabolic demands [ 66 ].…”
Section: The Role Of Mitochondrial Dysfunction In the Development Andsupporting
confidence: 74%
“…Fat accumulation in hepatocytes is the result of imbalanced fat metabolism, such as decreased mitochondrial lipid oxidation and enhanced synthesis of triglycerides. Therefore, the development of hepatic steatosis is associated with increased values of oxidative stress and structural defects in mitochondria (Sanyal et al 2001;Carabelli et al 2011), and it impacts mitochondrial respiration (Carabelli et al 2011). In this work, the activity of segments of the mitochondrial respiratory chain was analyzed in isolated hepatic mitochondria, thus accessing the sites in the respiratory chain on which inhibitions in response to diet occur.…”
Section: Discussionmentioning
confidence: 99%